Education for rural development and agribusiness in post-socialist Slovakia - Moravčíková, Danka; Adamičková, Izabela; Bielik, Peter (Applied Studies in Agribusiness and Commerce, 2013)
Agricultural education and training in the former Czechoslovakia has traditionally focused on fostering the position of cooperatives and state farms. The destruction of socialist agriculture and the reduction of commuting opportunities in the urban space during the transition have resulted in the handicapped socio-economic position of the Slovak countryside and its population. The role of education and training in fostering agribusiness growth and rural development could therefore become a crucial strategy. The aim of this article is to analyse the current state of education and training for agribusiness and for rural development in Slovakia using the methods of literature research and document analysis. The article interprets general trends in the development of adult education in Slovakia during the transition period. The main priorities and perspectives formulated in the national strategy for education in agriculture (for the period 2007-2013) are discussed in the mentioned context. With a focus on the leading role of the Slovak University of Agriculture in Nitra, the paper assesses the current status of formal and further agricultural education and training offered in academic and other educational institutions. The paper concludes by discussing implications, recommendations and challenges for developing education and training initiatives for agribusiness and rural development.